2015
DOI: 10.1159/000368601
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoamniotic Band Syndrome after In Utero Intervention for Twin-to-Twin Transfusion Syndrome: Case Reports and Literature Review

Abstract: Pseudoamniotic band syndrome (PABS) is a rare iatrogenic complication that arises after invasive procedures in monochorionic twins. We report 3 cases of PABS, 2 after fetoscopic laser photocoagulation and 1 after bipolar cord coagulation. Two cases were detected antenatally by ultrasound; out of the two, one underwent successful fetoscopic release of amniotic band, which is the first report in twin pregnancy to our knowledge. In our centre, the incidence of PABS was found to be 2%. There were 25 cases of PABS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 20 publications
1
26
0
2
Order By: Relevance
“…The survival rate without BA for at least one neonate in 52 cases was 94%. The incidence of complications related to FLP in women carrying sIUGR twins was lower than the incidence in those with TTTS [17-20]. Considering the extremely poor perinatal outcomes of those with abnormal UA Doppler waveforms and oligohydramnios undergoing conservative management [4, 5], FLP for these patients might possibly have a certain degree of effect.…”
Section: Discussionmentioning
confidence: 99%
“…The survival rate without BA for at least one neonate in 52 cases was 94%. The incidence of complications related to FLP in women carrying sIUGR twins was lower than the incidence in those with TTTS [17-20]. Considering the extremely poor perinatal outcomes of those with abnormal UA Doppler waveforms and oligohydramnios undergoing conservative management [4, 5], FLP for these patients might possibly have a certain degree of effect.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with a large retrospective analysis by Peeters et al [6] which found that patients with iatrogenic rupture of the intertwin membrane who were being treated for TTTS with laser surgery had a lower GA at birth and increased neonatal morbidity. Amniotic band formation is an additional complication seen in patients with disruption of the intertwin-dividing membrane in monochorionic multiple gestations [3, 8, 11, 14, 15]. …”
Section: Discussionmentioning
confidence: 99%
“…Pseudoamniotic band syndrome was diagnosed if there was evidence of amniotic bands on postoperative ultrasound or at delivery. Pseudoamniotic band syndrome is an iatrogenic complication after invasive in utero procedures where free-floating amniotic bands may be subsequently formed [11]. …”
Section: Methodsmentioning
confidence: 99%
“…56,66-69 Septostomy can be associated with amniotic membrane flaps and induce a pseudoamniotic band syndrome in 2-3% of the cases involving the limbs or the umbilical cord and leading to amputation and intrauterine death. 70 Therapeutic septostomy is controversial in TTTS but has been associated with an improvement of fetal and neonatal morbidity, also due to concomitant amniodrainage. 57,71 An intertwin membrane hematoma is a rare complication of DCDA twins generally associated with the development of a subchorionic hematoma under the insertion of the membrane.…”
Section: Obstetrics Expert Reviewsmentioning
confidence: 99%